Evaluation and optimization of mass transport of redox species in silicon microwire-array photoelectrodes - Xiang, Chengxiang (National Academy of Sciences, 2012)
Physical integration of a Ag electrical contact internally into a metal/substrate/microstructured Si wire array/oxide/Ag/electrolyte photoelectrochemical solar cell has produced structures that display relatively low ohmic resistance losses, as well as highly efficient mass transport of redox species in the absence of forced convection. Even with front-side illumination, such wire-array based photoelectrochemical solar cells do not require a transparent conducting oxide top contact. In contact with a test electrolyte that contained 50 mM/5.0 mM of the cobaltocenium(+/0) redox species in CH(3)CN–1.0 M LiClO(4), when the counterelectrode was placed in the solution and separated from the photoelectrode, mass transport restrictions of redox species in the internal volume of the Si wire array photoelectrode produced low fill factors and limited the obtainable current densities to 17.6 mA cm(-2) even under high illumination. In contrast, when the physically integrated internal Ag film served as the counter electrode, the redox couple species were regenerated inside the internal volume of the photoelectrode, especially in regions where depletion of the redox species due to mass transport limitations would have otherwise occurred. This behavior allowed the integrated assembly to operate as a two-terminal, stand-alone, photoelectrochemical solar cell. The current density vs. voltage behavior of the integrated photoelectrochemical solar cell produced short-circuit current densities in excess of 80 mA cm(-2) at high light intensities, and resulted in relatively low losses due to concentration overpotentials at 1 Sun illumination. The integrated wire array-based device architecture also provides design guidance for tandem photoelectrochemical cells for solar-driven water splitting.